Mathematical Modelling Concerning Compressibility of Air In Porosity During Semi-Dry Pressing Process Of Ceramic Powder - Shukhrat Shakirov,; Begali Bektemirov,; Sanobar Sadaddinova,; Ulugbek Umirov,; Mukhlisakhon Abdurakhmonova,; Kamoliddin Urokov,; Zukhra Mirzarakhimova, (International Journal of Integrated Engineering, 2025)
In this article, during the pressing of a cylindrical ceramic product from ceramic powder masses with a moisture content of 8...12%, the powder mass is considered as a model consisting of two: elastic (gas-air) and incompressible (mineral particle, water) phases. Based on this, a mathematical model was developed that depends on the initial properties of the powder mass, the allowable residual porosity in the structure of the ceramic product, and the displacement value of the punch during pressing during semi-dry pressing of the ceramic powder mass. This mathematical model allows for analytical calculations of gas-air compression level in powder pores, compressed air pressure, pressing force and pressure.